Innovating tourism in Merzouga: Gnawa music as a sustainability driver - Hiri, Abdelhak (2024)
This study proposes an innovative sustainable tourism model that promotes and preserves the Gnawa musical heritage in the Merzouga Desert, Morocco. The research aimed to develop and evaluate a community-based tourism model grounded in Gnawa music, fostering environmental sustainability and local empowerment. The hypothesis was that by integrating Gnawa music, this model would generate sustainable income for communities, strengthen Gnawa’s cultural identity, and significantly reduce the environmental impact of tourism in the area, thereby improving the quality of life of its inhabitants. A mixed approach was employed to achieve this objective, combining quantitative and qualitative methods. Surveys were also administered to tourists and tour operators to collect quantitative data, while in-depth interviews were conducted with key community stakeholders to gather qualitative information. This comprehensive approach allowed for a holistic analysis of the effects and potential of the proposed model.